Characterization of a stress tolerance‐defective mutant of Lactobacillus rhamnosus LRB. (7th June 2019) - Biswas, Saswati; Keightley, Andrew; Biswas, Indranil
Abstract: Lactobacillus rhamnosus is a lactic acid bacterium that survives diverse ecological niches, including the human oral cavity and gastrointestinal tract. L. rhamnosus is an acidogenic bacterium that produces copious amounts of lactic acid. The organism is also considered as aciduric, since it can survive prolonged exposure to an acidic environment. For a probiotic bacterium such as L. rhamnosus, it is necessary to understand how this organism survives acid stress. In this study we used L. rhamnosus LRB to isolate one spontaneous mutant that was sensitive to acid stress. The mutant, which we named RBM1, also displayed sensitivity to a wide range of stresses including osmotic, thermal, and others. Using whole genome sequencing, we mapped the putative mutations in the mutant strain. It appears that three single nucleotide substitutions occurred in the mutant as compared to the wild‐type LRB strain. Among those, the most relevant mutation occurred in the fts H gene that created a single amino acid change in the protein. We performed a comparative proteomic study to understand the molecular basis for stress sensitivity and found that 15% of the proteome is altered in the mutant strain. Our study suggests that generation of spontaneous mutants during L. rhamnosus colonization could drastically affect bacterial physiology and survival under stress conditions.